Evidence for Pleiotropic Effects of Statins in Clinical Trials - Liu, Ping-Yen; Wang, Chao-Yung; Liao, James K. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
Lipid-lowering agents, such as 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitors, also known as statins, have been shown to reduce cardiovascular events. However, evidence from recent clinical trials suggests that the beneficial effects of statins may be derived from both lipid lowering and non-lipid lowering, or “pleiotropic” effects. Animal studies suggest that some of these pleiotropic effects of statins are mediated by inhibition of Rho kinase (ROCK). ROCK has been shown important in regulation of vascular tone, cell proliferation, inflammation and oxidative stress. In the cardiovascular system, RhoA/ROCK pathway has also been implicated in angiogenesis, atherosclerosis, cerebral and coronary vasospasm, cerebral ischemia, hypertension, myocardial hypertrophy, and neointima formation after vascular injury. Indeed, in clinical studies, elevated ROCK activity is associated with cardiovascular risks and inhibition of ROCK leads to improved endothelial function. Therefore, modulation of the RhoA/ROCK pathway by statins may provide additional benefits beyond their lipid lowering effects, especially among high-risk cardiovascular patients.
Keywords: Statin